Common fixed points and invariant approximation of R-subweakly commuting maps in convex metric spaces - Chandok, S.; Narang, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Sufficient conditions for the existence of a common fixed point of R-subweakly commuting mappings are established within the framework of a convex metric space. As applications, we obtain various results on the best approximation for this class of mappings generalizing the results known from the literature.